Incentive mechanism of government overcommitment in PPPs based on investors’ fairness preference - Luo, Qi; Liu, Jicai (International Journal of Strategic Property Management, 2024)
In public-private partnerships (PPPs), governments sometimes may not afford the guarantees in full as initially agreed upon due to limited fiscal budgets. Accordingly, government overcommitment can occur. The degree of government overcommitment fulfillment affects not only the incentives provided by governments but also investors’ willingness to cooperate and efforts. However, until now, this government overcommitment risk has been ignored during negotiations. Moreover, little attention has been paid to the impact of investors’ fairness preference. To this end, this paper constructs an incentive mechanism of government overcommitment based on investors’ fairness preference in the horizontal and vertical dimensions. The results show that the optimal strategies of both sides are usually affected by the degree of government overcommitment fulfillment, investors’ fairness preference and their willingness to cooperate. Contrary to intuition, the optimal incentive of governments and investors’ efforts do not always increase with the decreasing degree of government overcommitment fulfillment, and thus, fairness preferences should be considered. It is not always the case that a higher-level government overcommitment fulfillment is better for themselves. The findings contribute new insights to the incentive mechanism to innovatively work toward creating an effective contract to pay more attention to government overcommitment risk in advance in PPPs.